Applicability of an in-House Saponin-Based Extraction Method in Bruker Biotyper Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry System for Identification of Bacterial and Fungal Species in Positively Flagged Blood Cultures - Chien, Jung-Yien; Lee, Tai-Fen; Du, Shin-Hei; Teng, Shih-Hua; Liao, Chun-Hsing; Sheng, Wang-Hui; Teng, Lee-Jene; Hsueh, Po-Ren (Frontiers in Microbiology, 2016)
We used an in-house saponin-based extraction method to evaluate the performance of the Bruker Biotyper matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS) system for the identification of bacteria and fungi in 405 positively flagged blood culture bottles. Results obtained from MALDI-TOF/MS were compared with those obtained using conventional phenotypic identification methods. Of the 405 positively flagged blood culture bottles, 365 showed monomicrobal growth and were correctly identified to the species (72.1%) or genus (89.6%) level using the Bruker Biotyper system. The remaining 40 positively flagged blood culture bottles showed polymicrobial growth. Of them, 82.5% (n=33) of the isolates were correctly identified to the species level and 92.5% (n=37) to the genus level using the Bruker Biotyper system. The overall accuracy of identification to the genus level in flagged blood cultures was 89.5% for Gram-positive organisms, 93.5% for Gram-negative pathogens and 71.9% for fungi. Confidence scores were 1.500 for 307 (75.8%) bottles, 1.700 for 249 (61.5%) bottles and 2.000 for 142 (35.1%) bottles. None of the yeast cultures yielded scores 1.700. Using an identification-score cutoff of 1.500, the MALDI Biotyper correctly identified 99.2% of Gram-positive bacteria, 97.6% of Gram-negative bacteria and 100% of yeast isolates to the genus level and 77.6% of Gram-positive bacteria, 87.1% of Gram-negative bacteria and 100.0% of yeast isolates to the species level. The overall rate of identification using our protocol was 89.9% (364/405) for genus level identification and 73.1% (296/405) for species level identification. Yeast isolates yielded the lowest confidence scores, which compromised the accuracy of identification. Further optimization of the protein extraction procedure in positive blood cultures is needed to improve the rate of identification.